CD33 Expression on Peripheral Blood Monocytes Predicts Efficacy of Anti-PD-1 Immunotherapy Against Non-Small Cell Lung Cancer - Olingy, Claire; Alimadadi, Ahmad; Araujo, Daniel J.; Barry, David; Gutierrez, Norma A.; Werbin, Max Hardy; Arriola, Edurne; Patel, Sandip Pravin; Ottensmeier, Christian H.; Dinh, Huy Q.; Hedrick, Catherine C. (Frontiers in Immunology, 2022)
Non-small cell lung carcinoma (NSCLC) is the leading cause of cancer-related deaths globally. Immune checkpoint blockade (ICB) has transformed cancer medicine, with anti-programmed cell death protein 1 (anti-PD-1) therapy now well-utilized for treating NSCLC. Still, not all patients with NSCLC respond positively to anti-PD-1 therapy, and some patients acquire resistance to treatment. There remains an urgent need to find markers predictive of anti-PD-1 responsiveness. To this end, we performed mass cytometry on peripheral blood mononuclear cells from 26 patients with NSCLC during anti-PD-1 treatment. Patients who were responsive to anti-PD-1 ICB displayed significantly higher levels of antigen-presenting myeloid cells, including CD9+ nonclassical monocytes, and CD33hi classical monocytes. Importantly, using matched pre-post treatment pairs for 10 patients, we found that the baseline pre-treatment frequencies of CD33hi monocytes predicted patient responsiveness to anti-PD-1 therapy. These classical and nonclassical monocyte subsets were associated with reduced immunosuppression of T regulatory (CD4+FOXP3+CD25+) cells in the same patients. Our use of machine learning corroborated the association of specific monocyte markers with responsiveness to ICB. Our work correlates CD33 expression on monocytes with anti-PD-1 therapy effectiveness and provides a high-dimensional profile of monocytes and monocyte-derived cells in NSCLC.